Educação financeira no ensino médio: jogos como instrumento de ensino - Konzen, Salete (2025)
This dissertation is based on the recognition that financial education is a fundamental component in the formation of young people, preparing them to face the economic challenges of adult life with responsibility and awareness. In the context of Basic Education, the inclusion of this topic is even more significant, as it offers students the opportunity to develop critical skills for making conscious and responsible financial decisions. However, teaching financial concepts such as financial planning and percentages can be abstract and challenging, requiring innovative didactic methods to make learning more meaningful and engaging. One relevant approach is the use of games as a pedagogical tool. When integrated into the teaching and learning process, games provide an interactive and practical experience that goes beyond the mere transmission of theoretical knowledge. Through entertainment and engagement, games facilitate the understanding of complex concepts in an accessible and attractive way, making learning more effective compared to conventional methods. Moreover, games encourage critical thinking and group dialogue, allowing students to share experiences, learn collectively, and foster an inclusive environment. Thus, the following research question is presented: How can the use of games support high school students in understanding concepts such as planning and percentages—essential to financial education—while promoting awareness that contributes to the development of healthy financial habits? Based on this, the general objective of this study is: To provide favorable conditions for understanding concepts such as planning and percentages, applied to financial education, through the use of educational games. The methodology of this study adopts a qualitative approach, and the technical procedures used are descriptive, constituting a case study that involves the analysis of categories, theoretically grounded in the contributions of Paulo Freire. The results show that the use of educational games in high school proves to be an effective pedagogical strategy for promoting financial education and raising young people’s awareness of the importance of developing healthy financial habits. Through the recreational nature of games, understanding fundamental concepts such as percentages becomes more accessible, while encouraging the development of responsible attitudes toward money management. Finally, the study highlights the relevance of the material developed in the form of an Educational Product, demonstrating its feasibility as a didactic resource for teaching Financial Mathematics. The material is available on the PPGECM/UPF page and in the EduCapes repository, at the address: http://educapes.capes.gov.br/handle/capes/1000942.